Surrogacy in Spain: a hard case needs law. Why jurisprudence can not solve this problem - Durán Ayago, Antonia (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
This paper is a balance of the ten years since the Resolution of the General Directorate of Registries and Notaries of February 18, 2009 wich for the first time authorized the registration in the Civil Registry of the children of a marriage of Spanish males who were born in the United States through surrogacy. Although this resolution was annulled, the facts that have been happening, with judicial different pronouncements in a certain way, require action by the legislator to clarify the situation and ensure the legal certainty of all those involved in a process of surrogacy, particularly of children born through this technique.